2023
DOI: 10.1152/japplphysiol.00271.2023
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit tracking using blind source separation filters and waveform cross-correlations: reliability under physiological and pharmacological conditions

Abstract: Recent advancements in the analysis of high-density surface electromyography (HDsEMG) have enabled the identification, and tracking, of motor units (MUs) to study muscle activation. This study aimed to evaluate the reliability of MU tracking using two common methods: blind source separation filters and two-dimensional waveform cross-correlation. An experiment design was developed to assess physiological reliability, and reliability for a drug intervention known to reduce the firing rate of motoneurones (cyproh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…MUs were tracked in the current study via the decomposition filter method, which has previously demonstrated high reliability during pharmacological interventions (Goodlich et al, 2023b). To investigate the effect of contraction type, MUs were tracked between the pre-drug 10% MVC trapezoid and pre-drug sombrero contractions.…”
Section: Motor Unit Trackingmentioning
confidence: 99%
“…MUs were tracked in the current study via the decomposition filter method, which has previously demonstrated high reliability during pharmacological interventions (Goodlich et al, 2023b). To investigate the effect of contraction type, MUs were tracked between the pre-drug 10% MVC trapezoid and pre-drug sombrero contractions.…”
Section: Motor Unit Trackingmentioning
confidence: 99%
“…Within each group, it was indeterminate whether one or multiple MUs were involved. In other studies involving the tracking of individual MUs, the MUAP waveform similarity was typically used and the performance of MUAP classification was only verified with isometric muscle contractions and fixed limb postures [6]- [16]- [20] where the MUAP waveforms were relatively stable. However, multiple factors, such as the MU firing rate [21]- [22], sustained muscle contractions [23] and electrode displacement [20], can induce the variation of MUAP profiles.…”
Section: Classification Of Action Potentials With High Variability Us...mentioning
confidence: 99%
“…While the cross-correlation coefficient is arguably a more common metric for MUAP tracking in isometric contractions [41][42][43], its use during dynamics should be treated with caution due to its insensitivity to amplitude changes. While Oliveira and Negro [15] pioneered its used to track MUAPs from the tibialis anterior between dynamic ankle dorsiflexions, their success may be explained by the limited range of motion explored (∼ 20 • ).…”
Section: Effect Of Dynamics In the Muapsmentioning
confidence: 99%